Development of a mobile-based software suite for the thermal and hydraulic design of heat exchangers - Shavin Shivaskar Kunasekaran (2017)
This final year project report is based on the development of a mobile application to aid the thermal and hydraulic designing of plate heat exchangers, with educational purposes and commercial potential in mind. The application was developed on the Apple iOS operating system, utilizing Objective-C programming language. The application was built and tested on Apple’s proprietary integrated development environment, i.e, Xcode. The main intention of selecting the Apple iOS platform was because many of the heat exchanger applications have been developed solely for Android and desktop operating systems. This application behaves as a foundation for heat exchanger applications in the Apple world and provides vast opportunities to venture deeper into the development of such educational and commercial applications.